学习文档 仅供参考
不等式
5X-2≥3〔X+1〕
3x(x+5)>3x2+7
x-4 < 2x+1
3x+14 > 4(2x-9)
3x-7≥4x-4
学习文档 仅供参考
不等式
5X-2≥3〔X+1〕
3x(x+5)>3x2+7
x-4 < 2x+1
3x+14 > 4(2x-9)
3x-7≥4x-4
2x-3x-3<6
(x-1)≥-
x-4 < 2x+1
2x-6 < x-2
3×10x<500
7〔X+3〕>98
2x-3x+3<6
2x-3x+1<6
2x-3x+3<1
2x-19<7x+31
3x-2(9-x)>3(7+2x)-(11-6x)
2(3x-1)-3(4x+5)≤x-4(x-7)
2(x-1)-x>3(x-1)-3x-5
15-(7+5x)≤2x+(5-3x)
4〔2X-3〕>5〔X+2〕
2X+4<0
5X-2≥3〔X+1〕
2〔X-3〕≤4
5m-3>0
2x-3(x-1) > 6
6x-3(x-1) ≤12-2(x+2)
3(1-3x) < 4(x-1)
8-7x+1 > 2(3x-2)
3x+14 > 4(2x-9)
3-3m<-2m
5x+3x>2
-3y+9<7
(3+8)x>6
5-3/1 x>5
11x-5x>3
-3a-9a>11
-4a+9>6
33x+33<1
5b-9<9b
6x+8>3x+8
3x-7≥4x-42x-19<7x+31.
3x-2(9-x)>3(7+2x)-(11-6x).
2(3x-1)-3(4x+5)≤x-4(x-7).
学习文档 仅供参考
2(x-1)-x>3(x-1)-3x-5.
3[y-2(y-7)]≤4y.
15-(7+5x)≤2x+(5-3x).
3*10(x+1)>500
7〔x+3〕>98
8-7X>4-5X
2〔1+X〕>3〔X-7〕
4〔2X-3〕>5〔X+2〕
3x-2(9-x)>3(7+2x)-(11-6x)
2(3x-1)-3(4x+5)≤x-4(x-7)
2(x-1)-x>3(x-1)-3x-5
3[y-2(y-7)]≤4y
15-(7+5x)≤2x+(5-3x)
20x-3≤5x+(x-5)
7x-2(x-3)<16
3(2x-1)<4(x-1)
5-x(x+3)>2-x(x-1)
3-4[1-3(2-x)] >59
4x-10<15x-(8x-2)
3(6+x)>6(X+3)
2/3(x+6-9)<5(-x+9)
3x(x+5)>3x2+7
3x+14 > 4(2x-9)
3x-7≥4x-4
2x-3x-3<6
(x-1)≥-
7〔X+3〕>98
2x-3x+3<6
2x-3x+1<6
2x-3x+3<1
2x-19<7x+31
3x-2(9-x)>3(7+2x)-(11-
一元一次不等式计算题 来自淘豆网m.daumloan.com转载请标明出处.